Real communities of virtual plants explain biodiversity on just three assumptions. Issue 1 (25th March 2021) - Hunt, Roderick; Colasanti, Ric L
Abstract: To illuminate mechanisms supporting diversity in plant communities, we construct 2D cellular automata and 'grow' virtual plants in real experiments. The plants are 19 different, fully validated functional types drawn from universal adaptive strategy theory. The scale of approach is far beyond that of even the most ambitious investigations in the physical world. By simulating 496 billion plant–environment interactions, we succeed in creating conditions that sustain high diversity realistically and indefinitely. Our simulations manipulate the levels of, and degree of heterogeneity in the supply of, resources, external disturbances and invading propagules. We fail to reproduce this outcome when we adopt the assumptions of unified neutral theory. The 19 functional types in our experiments respond in complete accordance with universal adaptive strategy theory. We find that spatial heterogeneity is a strong contributor to long-term diversity, but temporal heterogeneity is less so. The strongest support of all comes when an incursion of propagules is simulated. We enter caveats and suggest further directions for working with cellular automata in plant science. We conclude that although (i) the differentiation of plant life into distinct functional types, (ii) the presence of environmental heterogeneity and (iii) the opportunity for invasion by propagules can all individually promote plant biodiversity, all three appear to be necessary simultaneously for its long-term maintenance. Though further, and possibly more complex, sets of processes could additionally be involved, we consider it unlikely that any set of conditions more minimal than those described here would be sufficient to deliver the same outcome. Graphical Abstract: